2013
DOI: 10.1038/srep03058
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of novel H7N9 influenza A virus to human receptors

Abstract: The emergence of the novel H7N9 influenza A virus (IAV) has caused global concerns about the ability of this virus to spread between humans. Analysis of the receptor-binding properties of this virus using a recombinant protein approach in combination with fetuin-binding, glycan array and human tissue-binding assays demonstrates increased binding of H7 to both α2-6 and α2-8 sialosides as well as reduced binding to α2-3-linked SIAs compared to a closely related avian H7N9 virus from 2008. These differences could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
77
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 44 publications
(75 reference statements)
7
77
1
1
Order By: Relevance
“…1B and F). This is in agreement with the results of a study by Shi et al, which showed that the L217Q substitution in the AN1 HA did not completely abrogate human receptor binding, implying that other substitutions in the RBS might contribute to the ␣2,6-linked SA binding of AN1 (3,16). Moreover, the G219S substitution significantly increased overall binding affinities to ␣2,3-and ␣2,6-linked SA ( Fig.…”
Section: R Ecent Human Infections With Influenza A/h7n9 Viruses Insupporting
confidence: 92%
“…1B and F). This is in agreement with the results of a study by Shi et al, which showed that the L217Q substitution in the AN1 HA did not completely abrogate human receptor binding, implying that other substitutions in the RBS might contribute to the ␣2,6-linked SA binding of AN1 (3,16). Moreover, the G219S substitution significantly increased overall binding affinities to ␣2,3-and ␣2,6-linked SA ( Fig.…”
Section: R Ecent Human Infections With Influenza A/h7n9 Viruses Insupporting
confidence: 92%
“…Previously, we and others generated recombinant soluble NA proteins for structure determination, enzymatic activity, and immunogenicity analyses (22)(23)(24)(25)(26)(27)(28)(29)(30). The use of recombinant soluble glycoproteins provides several advantages.…”
mentioning
confidence: 99%
“…In view of the importance of NA oligomerization for enzymatic activity, N-terminal tetramerization domains are generally fused to the recombinant soluble NA proteins. These tetramerization domains may be artificial, like GCN4-pLI (22,23), or derived from bacterial or mammalian proteins, such as the Staphylothermus marinus Tetrabrachion protein (27,28) or human vasodilatorstimulated phosphoprotein (VASP) (24,29,30). Although the recombinant soluble NA proteins have been used for different analyses, it is not known how the different N-terminal oligomerization domains affect NA protein assembly and enzymatic properties.…”
mentioning
confidence: 99%
“…Structural and receptor binding analyses have demonstrated that the H7N9 viruses bind to both avian-like ␣2,3-linked sialic acid (SA) receptors and mammalian-like ␣2,6-linked SA receptors. The Q226L change, which has been associated with reduced binding to ␣2,3-SA and increased binding to ␣2,6-SA (16,17), and other residues in the H7N9 HA contribute to this receptor binding specificity (13,(18)(19)(20). Although sustained human-tohuman transmission has not been reported, the H7N9 virus can be transmitted via aerosol in ferrets, raising concerns about its pandemic potential (21)(22)(23).…”
mentioning
confidence: 99%